Inklusi Keuangan Syariah di Era Digital antara Peluang dan Tantangan Islamic Social Finance dalam Menjangkau Masyarakat Unbankable - Muchammad Iqbal Fatah Muchammad Iqbal Fatah (Cashless : Journal of Sharia Finance and Banking, 2026)
Financial inclusion is a strategic agenda in national economic development, particularly in efforts to reach groups of people who have been excluded from formal banking services (the unbankable). Islamic Social Finance (ISF), which encompasses zakat, infaq, sedekah, and productive waqf (ZISWAF) instruments, has great potential as an inclusive alternative based on Islamic values. In the digital era, technological transformation through sharia fintech, digital waqf platforms, and app-based financial services opens up opportunities for expanding ISF's reach more broadly and efficiently. However, various structural challenges such as low digital literacy, infrastructure gaps, and a suboptimal regulatory framework remain significant obstacles. This study uses a qualitative approach with library research methods to examine the opportunities and challenges of digital ISF in promoting sharia financial inclusion for the unbankable community. The results indicate that the synergy between digital technology and ISF instruments has the potential to become a significant inclusive solution, provided there is strengthening literacy, improving regulations, and collaboration across stakeholders.